2020
DOI: 10.3390/su12145833
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Employees’ Affective Commitment: A Moderated Mediation Study

Abstract: Corporate Social Responsibility (CSR) has mainly been studied at a macro level through its impact on the financial performance of the company. However, individuals’ perceptions of CSR influence various attitudes and behaviors at work, including employees’ affective commitment. Whereas the relationship between perceptions of CSR and employees’ affective commitment has already been shown in the literature, less is known about its underlying mechanisms. This research seeks to specifically explain this relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 98 publications
(142 reference statements)
1
45
0
2
Order By: Relevance
“…As it concerns customers, CSR has been linked to consumer satisfaction (Bhattacharya & Sen, ) and customer extra‐role behavior (Lii & Lee, ; Hur, Kim & Kim, ). More recently, studies have looked at the impact of CSR on employees by looking at many organizational behavior variables, for example, employee‐company identification (McShane & Cunningham, ), organizational commitment (Bouraoui, Bensemmane, Ohana, & Russo, ), organizational citizenship behaviors (Ong, Mayer, Tost, & Wellman, ), general satisfaction (Valentine & Fleischman, ), turnover intention (Hansen, Dunford, Boss, Boss, & Angermeier, ), turnover (Ng, Yam, & Aguinis, ), team performance (Lin, Baruch, & Shih, ), job satisfaction (Zhou, Luo, & Tang, ), engagement (Rupp et al, ), and organization identification (De Roeck & Delobbe, ; Ghosh, ).…”
Section: Introductionmentioning
confidence: 99%
“…As it concerns customers, CSR has been linked to consumer satisfaction (Bhattacharya & Sen, ) and customer extra‐role behavior (Lii & Lee, ; Hur, Kim & Kim, ). More recently, studies have looked at the impact of CSR on employees by looking at many organizational behavior variables, for example, employee‐company identification (McShane & Cunningham, ), organizational commitment (Bouraoui, Bensemmane, Ohana, & Russo, ), organizational citizenship behaviors (Ong, Mayer, Tost, & Wellman, ), general satisfaction (Valentine & Fleischman, ), turnover intention (Hansen, Dunford, Boss, Boss, & Angermeier, ), turnover (Ng, Yam, & Aguinis, ), team performance (Lin, Baruch, & Shih, ), job satisfaction (Zhou, Luo, & Tang, ), engagement (Rupp et al, ), and organization identification (De Roeck & Delobbe, ; Ghosh, ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing this level of adaptation can enable the individual to participate more or, in other words, increase affective commitment. For example, in a recent study, Bouraoui et al [18] found that employees' perception of CSR (based on how well they perceive the fit with their organizations) can determine their affective commitment. When the effects of organizations' CSR practices on the organizations' stakeholders are compared, the level of observation or influence of all other stakeholders except employees can be indirect [38].…”
Section: Csr and Affective Commitmentmentioning
confidence: 99%
“…A successful CSR strategy should be embedded in the organizational core competencies and integrated within the firm's strategy, routines, and operations [15], including HR. However, there is still ambiguity concerning the understanding of the microfoundations of CSR [16][17][18], particularly mechanisms that explain the underlying effects of how CSR activities are perceived by the employees [16][17][18]. Studies have claimed that employee perceptions towards CSR practices may affect employees' subsequent behavior towards the organization [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…From the 1990s until the present moment, organizational commitment has been one of the most studied employee attitudes in management literature (Bouraoui, Bensemmane, Ohana, & Russo, 2019;Meyer, Stanley, Herscovitch, & Topolnytsky, 2002). The term refers to employees' attachment to an organization and identification with its goals (Dalal & Crede, 2013, p. 681).…”
Section: Organizational Commitmentmentioning
confidence: 99%